2020
DOI: 10.3390/brainsci10070425
|View full text |Cite
|
Sign up to set email alerts
|

Neck Pain- and Unsteadiness-Inducing Activities and their Relationship to the Presence, Intensity, Frequency, and Disability of Headaches

Abstract: (1) Background: Headache is a significant public health problem. Despite the association between headache and neck pain, little is known about the relationships among specific activities that generate neck pain and headache. The aim of this study was to identify the specific activities that result in neck pain and unsteadiness, and determine how they are linked to headache in university students. (2) Methods: One hundred and six patients with physician-diagnosed headache and 92 healthy university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The main reason for these results possibly reflects the important role that cervical, vestibular, and visual structures play in both the perception of verticality and the physio-pathological processes of primary headaches. A recent study revealed the concomitance of neck pain-generating activities, instability-inducing activities, and primary headaches, where high visual attention-demanding activities are essential in this process [ 59 ]. VV misperception in patients with PHD may be facilitated by alterations in some of the three systems involved in forming the pattern of central verticality (vestibular, visual, and somatosensory systems).…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for these results possibly reflects the important role that cervical, vestibular, and visual structures play in both the perception of verticality and the physio-pathological processes of primary headaches. A recent study revealed the concomitance of neck pain-generating activities, instability-inducing activities, and primary headaches, where high visual attention-demanding activities are essential in this process [ 59 ]. VV misperception in patients with PHD may be facilitated by alterations in some of the three systems involved in forming the pattern of central verticality (vestibular, visual, and somatosensory systems).…”
Section: Discussionmentioning
confidence: 99%